Human–Wildlife Conflict and Ease of Living: Administrative Efficiency and Grievance Redressal in Environmentally Sensitive Districts in Kerala - Malavika Vijayan; Goutham Sankar P. (Indian Journal of Public Administration, 2026)
Human Wildlife Conflict (HWC) is often treated as an ecological or law-and-order problem, but in environmentally sensitive districts, it is experienced by citizens primarily as an everyday governance and administrative issue. This qualitative case study of forest-border areas examines how the impact of HWC on the ease of living of citizens is mediated not merely by the frequency of incidents but by the efficiency and accessibility of grievance redressal and compensation processes within forest administration. The article identifies key administrative burdens—learning, compliance and psychological costs—embedded in current procedures and shows how street-level discretion and institutional bottlenecks shape who receives timely, adequate relief. The analysis reconceptualises ease of living as a lived experience of citizen–state interaction, rather than an index score, and proposes concrete process reforms: simplification of compensation procedures, inter-departmental convergence, time-bound grievance resolution and trust-building practices in forest governance.